Rasam Balia in the Palu Nomoni Festival in Palu, Central Sulawesi in Sadd Adz-Dzari'ah’s Perspective - Lebba Lebba; Djafar Abidin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2021)
The main objective of this research is to give a description, implications, and review sadd Al-Dzarī’ah against ritualistic Rasam Balia in Palu Nomoni festival in Palu, Central Sulawesi province. The method of approach used is qualitative in several ways, namely through data collection (by observation, interview and documentation techniques), data management (through e- coding, coding, frequency counting, tabulation, verification, and data analysis). One of the results of this study is a description of the Balia Rasam ritual at the Palu Nomoni festival in the city of Palu in the province of Central Sulawesi is a. This activity was conducted by government of Palu as an annual festival, international level with participant that come from local communities, national and International. b. The event conducted for one week every September, c. The ritual becomes a must in Palu Nomoni festival with the purpose of healing, enhancing provision, refuse bad luck, and for safety. d. Its special uniform (black mixed red / yellow), the head tied with a black cloth, face, lips and hands in painted with colourful paint that shows the horrors, It filled with dance till the morning like people being possessed and drunk, chew bark, iron, razor blades, wood, stabbed the animal’s neck until it bled and then the blood was drunk and washed into the high seas.